Prevalence of Anemia and Its Associated Factors Among Adult Diabetes Mellitus Patients at Debre Tabor General Hospital, Northcentral Ethiopia - Engidaw, Melaku Tadege (Diabetes Metab Syndr Obes, 2020)
BACKGROUND: Diabetes mellitus is a cluster of metabolic disorders which is characterized by hyperglycemia. The occurrence of anaemia is a significant public health problem among diabetic patients because of complication and dietary modifications. So, this study aimed to assess the magnitude of anaemia among adult diabetes mellitus patients in Debre Tabor General Hospital, Ethiopia. METHODS: A cross-sectional study design was conducted. A simple random sampling technique was employed to collect data from 297 adult diabetic mellitus patients. After taking venous blood, the haemoglobin level was determined by using HemoCue 301 machine. Anaemia among diabetic patients was determined by using the haemoglobin level (<13.0g/dL for male and <12.0g/dL for female). Data were entered using EpiInfo version 7.2 and analyzed using SPSS version 21. The binary logistic regression model was used to explore the association of independent variables with anaemia. Finally, p-value <0.05 was used to declare the level of statistical significance. RESULTS: The prevalence of anemia among diabetic patient was 29.81% (95% CI: 24.27, 35.35). Diabetic patients unable to read and write (AOR = 3.51, 95% CI: 1.40, 8.75), able to read and write (AOR = 9.76, 95% CI: 3.15, 30.24), ≥4 family size (AOR = 0.53, 95% CI: 0.29, 0.99), intake of flesh meat (AOR=0.19, 95% CI: 0.05, 0.74), and parasitic infections (AOR = 0.26, 95% CI: 0.07, 0.95) were more likely to develop anemia. CONCLUSION: Anemia is a moderate public health problem among diabetic patients. Here, educational status, family size, intake of flesh meat, and intestinal parasite infections were the factors associated with the development of anaemia. So, working on these significant factors by health care providers during routine care is vital to prevent anaemia among diabetic patients.